A Thermoelastic Asperity Contact Model Considering Steady-State Heat Transfer - Wang, Qian (Jane); Liu, Geng (Tribology transactions, 1999)
One of the important issues in mixed lubrication is the contact problem involving frictional heating in the interface of contacting bodies. Due to contact and rubbing, temperature in the solid media varies, causing the contact conditions to change as a consequence of thermal distortion. A thermoelastic model for rough surfaces is developed for asperity contact subject to steady-state heat transfer. In this model, asperity distortion due to thermal and elastic-plastic deformations is considered. The thermal deformation is related to the contact pressure through a thermal influence function. Matrices for thermal and elastic influence functions are solved with the finite element method and the contact problem is computed with a mathematical programming method. Numerical analyses on the thermoelastic contact involving a rough surface reveal that asperity thermal distortion affects the contact pressure and surface separation at high frictional heat and deep asperity penetration. Presented at the 54th Annual Meeting Las Vegas, Nevada May 23-27, 1999